Reimagining terrain vague: the adaptive re-use of Makwassie’s Train Station as an agricultural centre - Rheeder, Eugenie (University of the Free State, 2021)
Situated on the periphery of a small town in North-West a decaying train station stands idle. Between open veld and a small town where nothing has changed over the last 50 years lies potential for an architectural intervention. This dissertation will address the revitalization of a static industrial site. This industrial site has lost its original identity and fallen victim to deterioration. A loss in original identity created a site that is vague. Revitalization of vague sites can be achieved by exploring the latent potentials within the site narrative. The intervention confronts the transitions between the dynamic environmental transformations of the site and the static structures on site. The study examines the importance of adaptively re-using structures. This intervention will be manifested as an agricultural centre. The aim is to re-activate the terrain through the layering of transitions in the program activating the inherent sense of place.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2021
Keywords: Makwassie’s train station; Revitalization of vague sites; Agricultural centre; Revitalization industrial site